2003
DOI: 10.1074/jbc.m304718200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Store-operated Calcium Channels

Abstract: Store-operated calcium channels (SOC) play a central role in cellular calcium homeostasis. Although it is well established that SOC are activated by depletion of the endoplasmic reticulum calcium stores, the molecular mechanism underlying this effect remains ill defined. It has been suggested that SOC activation requires fusion of endomembrane vesicles with the plasmalemma. In this model, SNARE-dependent exocytosis is proposed to deliver channels or their activators to the surface membrane to initiate calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 48 publications
0
2
1
Order By: Relevance
“…A potential role for vesicular transport in SOCE was also implied through the effect of interventions that altered the cortical cytoskeleton (Patterson et al, 1999;Rosado et al, 2000). More specific approaches targeted at inhibiting different components of the SNARE machinery required for vesicular fusion also produced conflicting results (Yao et al, 1999;Alderton et al, 2000;Bakowski et al, 2003;Scott et al, 2003). It is difficult to reconcile these early findings with our current knowledge of the SOCE activation mechanism centered around STIM1-Orai1 modulation and interaction.…”
Section: Identity Of the Orai1-positive Endosomal Compartmentscontrasting
confidence: 45%
“…A potential role for vesicular transport in SOCE was also implied through the effect of interventions that altered the cortical cytoskeleton (Patterson et al, 1999;Rosado et al, 2000). More specific approaches targeted at inhibiting different components of the SNARE machinery required for vesicular fusion also produced conflicting results (Yao et al, 1999;Alderton et al, 2000;Bakowski et al, 2003;Scott et al, 2003). It is difficult to reconcile these early findings with our current knowledge of the SOCE activation mechanism centered around STIM1-Orai1 modulation and interaction.…”
Section: Identity Of the Orai1-positive Endosomal Compartmentscontrasting
confidence: 45%
“…In addition, the immunoblot analysis unequivocally showed that SNAP25 as well as SNAP23 is expressed in HeLa cells ( ), although previous studies reported that SNAP25 was expressed predominantly in neuronal tissues while SNAP23 was expressed ubiquitously ( Ravichandran et al, 1996 ; Scott et al, 2003 ).…”
Section: Resultsmentioning
confidence: 87%
“…The dominant-negative mutants of transmembrane domain (TMD)-containing SNAREs were constructed by deleting the TMD by PCR-based methods. The mutants of TMDless SNAREs (STX11, SNAP23, SNAP29, and Ykt6) were generated according to previous studies (Scott et al, 2003;Fukasawa et al, 2004;Offenhäuser et al, 2011). For BiFC, Vn (aa 1-172) and Vc (aa 154-236) fragments of Venus were fused with the N-terminus of Bet1 and the C-terminus of MT1-MMP, respectively, in the pCI vector (Promega).…”
Section: Dna Constructs Sirnas and Transfectionmentioning
confidence: 99%